Ileocecal intestine as an alternative material for restoration of esophageal and vocal functions in cancer patients after laryngectomy (literature review) - A. M. Svirnovskaya; M. V. Ratushniy; A. Р. Polyakov (Опухоли головы и шеи)
The ileocolon flap is a promising plastic material for one-stage restoration of the nutrition and voice functions in cancer patients after laryngectomy and laryngopharyngectomy. The advantage of using this flap over alternative visceral flaps is its anatomical and functional features, the presence of its own one-way valve that assists in the passage of air from the trachea to the pharynx, prevents regurgitation of food or saliva into the respiratory tract and thereby ensures the restoration of vocal function without the need for additional devices. This review analyzes the use of ileocolon flap in the reconstruction of the upper aerodigestive tract, its advantages over other methods, as well as thе role of this approach in improving the quality of life of patients. Historical aspects, technical features, factors influencing the choice of technique, and the results of clinical studies confirming the effectiveness and reliability of this reconstruction method are considered.